The Effectiveness of the Problem-Based Learning Model in Enhancing Critical Thinking Skills in Science Education - Mooduto, Yulanti S (Journal La Edusci, 2025)
This study evaluates the effectiveness of the Problem-Based Learning (PBL) model in enhancing critical thinking skills in elementary school Science education. The research was conducted in the Pulubala District, involving two groups: an experimental group using the PBL model and a control group following conventional teaching methods. A quantitative experimental design was adopted, with pre-test and post-test assessments to measure the change in students’ critical thinking skills. Data analysis was performed using paired t-tests to examine the significant differences in pre-test and post-test scores between the two groups. Descriptive statistics indicated that the experimental group had an average pre-test score of 78.13, which increased to 89.20 in the post-test, with a reduction in standard deviation (SD) from 4.97 to 3.90, showing improved consistency in student understanding. In contrast, the control group showed an increase from 74.13 in the pre-test to 82.67 in the post-test, with a slightly higher SD of 4.19 in the pre-test and 3.90 in the post-test. Paired t-test results showed a significant difference in the experimental group (t-value = 10.75, p-value = 0.000) compared to the control group (t-value = 5.29, p-value = 0.000). The study also evaluated teachers’ competency in implementing PBL, revealing strong performance in most categories, though challenges in classroom management and student engagement need addressing. The study concludes that the PBL model is effective in enhancing critical thinking skills in elementary Science education and offers a viable alternative to improve teaching quality at the elementary level.